2012
DOI: 10.1155/2012/313781
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Potential of Manuka Honey and Platelet-Rich Plasma in Wound Healing

Abstract: Aim. The purpose of this study was to determine the in vitro response of cells critical to the wound healing process in culture media supplemented with a lyophilized preparation rich in growth factors (PRGF) and Manuka honey. Materials and Methods. This study utilized cell culture media supplemented with PRGF, as well as whole Manuka honey and the medical-grade Medihoney (MH), a Manuka honey product. The response of human fibroblasts (hDF), macrophages, and endothelial cells (hPMEC) was evaluated, with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 57 publications
10
86
0
3
Order By: Relevance
“…Enhancement of dermal regeneration potential was evident. 56 The effect of wound healing may be a culmination of both the anti-inflammatory effect, anti-microbial as well as immunostimulatory effect of manuka honey. Immuno-stimulation, in particularly the elevated level of cytokine hormones is merited as one mechanism for wound repair.…”
Section: Anti-ulcer and Wound Healingmentioning
confidence: 99%
“…Enhancement of dermal regeneration potential was evident. 56 The effect of wound healing may be a culmination of both the anti-inflammatory effect, anti-microbial as well as immunostimulatory effect of manuka honey. Immuno-stimulation, in particularly the elevated level of cytokine hormones is merited as one mechanism for wound repair.…”
Section: Anti-ulcer and Wound Healingmentioning
confidence: 99%
“…This leads to ECM reinforcement, fibroblast proliferation, and the synthesis and accumulation of collagen, all of which are essential for wound healing . For horses, PRP application induces more rapid epithelial differentiation, increasing collagen presence, and collagen matrix contraction, causing dense collagen bundles to be oriented parallel to each other and to the overlying epithelium, which is required for wound healing …”
Section: Newer Treatments For Pressure Ulcersmentioning
confidence: 99%
“…These influences appear to result from platelet release of VEGF, PDGF, and TGF‐β3. 72 The influences of PRP are enhanced when it is combined with manuka honey . This suggests that combining PRP with other techniques may induce more rapid and extensive ulcer healing.…”
Section: Newer Treatments For Pressure Ulcersmentioning
confidence: 99%
“…Recent research has indicated that lyophilized PRP (i.e. a preparation rich in growth factors, PRGF) may contain a number of MAC phenotype modifying biomolecules (IL-10, lipoxins) [31][32][33]. It has been suggested that PRP possesses the ability to modify the local inflammatory response and stimulate healing in chronic pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%